Time-Optimal Path Tracking for Robots: A Convex Optimization Approach - Verscheure, D.; Demeulenaere, B.; Swevers, J.; De Schutter, J.; Diehl, M. (IEEE transactions on automatic control, 2009)
This paper focuses on time-optimal path tracking, a subproblem in time-optimal motion planning of robot systems. Through a nonlinear change of variables, the time-optimal path tracking problem is transformed here into a convex optimal control problem with a single state. Various convexity-preserving extension are introduced, resulting in a versatile approach for optimal path tracking. A direct transcription method is presented that reduces finding the globally optimal trajectory to solving a second-order cone program using robust numerical algorithms that are freely available. Validation against known examples and application to a more complex example illustrate the versatility and practicality of the new method.